Mutual influences between memory and attention - Roüast, NM (2021)
Memory and attention are two of the most fundamental components of our cognition. Crucially, they do not operate independently but instead display an intricate, interactive relationship: our memories can guide our attention, and our attentional focus can shape our emerging memories. The aim of this doctoral thesis was to illuminate these mutual influences between memory and attention during the three crucial stages of memory establishment: encoding, consolidation, and retrieval. After delineating the scope of the thesis and defining relevant concepts and terminology in an introductory chapter (Chapter I), three experimental chapters discuss work exploring the memory attention interplay at these three stages.